2009
DOI: 10.1002/cjoc.200990122
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis and Characterization of Monodisperse Fe3O4 Nanoparticles

Abstract: Monodisperse Fe 3 O 4 nanoparticles were successfully synthesized through the thermal decomposition of iron acetylacetonate in octadecene solvent in the presence of oleic acid and oleylamine. The influences of experimental parameters, such as reacting temperature, amounts and kinds of surfactants, solvents, oleic acid and oleylamine, on the size and shape of monodisperse Fe 3 O 4 nanoparticles were discussed. The phase structures, morphology, and size of the as-prepared products were investigated in detail by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It has been reported that the OAm/OAc pair also helps to prevent, to some extent, further particle oxidation. 22 If polypyrrole or poly( N -methylpyrrole), which is used as a reductant, is combined with OAm/OAc, ordered lamellar nanostructures would be impressively observed, probably via a template growth assisted by the OAc molecules. 23 Sun's group reported in 2009 that the utilization of excess OAm is important to ensure a strongly reductive environment for the thermal decomposition of iron acetylacetonate.…”
Section: Iron Oxide Metal Ferrite and Other Oxide Nanoparticles Prepa...mentioning
confidence: 99%
“…It has been reported that the OAm/OAc pair also helps to prevent, to some extent, further particle oxidation. 22 If polypyrrole or poly( N -methylpyrrole), which is used as a reductant, is combined with OAm/OAc, ordered lamellar nanostructures would be impressively observed, probably via a template growth assisted by the OAc molecules. 23 Sun's group reported in 2009 that the utilization of excess OAm is important to ensure a strongly reductive environment for the thermal decomposition of iron acetylacetonate.…”
Section: Iron Oxide Metal Ferrite and Other Oxide Nanoparticles Prepa...mentioning
confidence: 99%
“…However, using the solvothermal method and similar raw materials as the system, some studies in the literature reported that the synthesized Fe 3 O 4 nanoparticles have different results in monodispersity and superparamagnetism compared to the aforementioned literature [32][33][34][35][36][37][38][39][40]. Li [41] used anhydrous ferric chloride as the iron source, ethylene glycol as the solvent, and sodium citrate as the surfactant, and the particle size was adjusted by varying the amount of sodium citrate.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the flame-retardant properties of materials could be improved by the incorporation of flame retardants. [7][8][9] Referring to the past studies on TPU, it was found that halogen-containing flame retardants, especially bromine and chlorine compounds, once were the most widely used organic flame retardants because of their high flameretardant efficiency and high price performance. However, dense smoke and corrosive, toxic gases are produced during the pyrogenation and combustion process for materials treated with halogen-containing flame retardants, causing environmental problems or fatal injuries to people in disastrous fires, [10,11] which is contrary to the environmental protection requirements.…”
Section: Introductionmentioning
confidence: 99%